2005
DOI: 10.1111/j.1365-2214.2005.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, socio‐demographic, neurophysiological and neuropsychiatric evaluation of children with volatile substance addiction

Abstract: In our study, neurophysiological and neuropsychiatric tests revealed that toluene causes slow progressive, clinical and subclinical central and peripheral nerve damage. In Turkey, because of cheapness, easy availability and legal use of volatile substances, the clinical extent of systemic and neurological toxicity of volatile substance abuse is increasing. Abuse of volatile substances, a currently increasing social issue, may create important physical problems which can be permanent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Glue and thinner sniffing are the most common forms of inhalant use. Thinner produced in our country (Turkey) contains 90% toluene, 9% ethyl acetate, and less than 1% benzol, and the main solvent of the substance used as glue is toluene [10]. Thinners contain more of toluene as compared to glues.…”
Section: Introductionmentioning
confidence: 99%
“…Glue and thinner sniffing are the most common forms of inhalant use. Thinner produced in our country (Turkey) contains 90% toluene, 9% ethyl acetate, and less than 1% benzol, and the main solvent of the substance used as glue is toluene [10]. Thinners contain more of toluene as compared to glues.…”
Section: Introductionmentioning
confidence: 99%
“…While pharmaceutical drugs present a major problem for child poisonings throughout the world, abuse of volatile substances including glue, aerosol sprays and fuel is also problematic . Children who abuse these substances experience progressive systemic and neurological toxicity, with potentially irreversible physical consequences . While homelessness increases volatile substance abuse , so too do certain cultural factors .…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological research suggests that inhalant users manifest poor working memory and abstract reasoning, poor visual–spatial recall and processing speed (Saddik et al . 2005; Uzun & Kendirli 2005; Lubman et al . 2008; Yücel et al .…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with heightened drug cravings, drug seeking and greater drug consumption in comparison with non-inhalant users (Borne et al 2005;Riegel et al 2007). Neuropsychological research suggests that inhalant users manifest poor working memory and abstract reasoning, poor visual-spatial recall and processing speed (Saddik et al 2005;Uzun & Kendirli 2005;Lubman et al 2008;Yücel et al 2008) Many of the existing inhalant abuse studies used retrospective designs (Howard et al 2008), analysed national or local population databases or reported individual case study findings (Wu & Howard 2007). Many inhalant abuse studies used smaller number of participants, did not compare cognitive or psychosocial functioning between inhalant and non-inhalant users, did not formally assess the interaction of drug use severity (the quantity and types of drugs used), and failed to mention that inhalant users are not a homogenous group, but the majority of inhalant users are also using other substances.…”
Section: Introductionmentioning
confidence: 99%